Analysing Elfriede Jelinek’s The Piano Teacher: The Layers of Erika’s Masochism - Yucel, Ecem (Université d'Ottawa | University of Ottawa, 2018)
Elfriede Jelinek‘s highly controversial novel The Piano Teacher introduces its protagonist Erika Kohut, a thirty-eight-year-old piano teacher who works at the prestigious Vienna Conservatory. As the book follows the story of Erika, Jelinek reveals her protagonist‘s underlying sadistic, masochistic, voyeuristic, phallic and even fetishistic layers. This paper aims to examine these layers of Erika‘s personality, associated with her most significant feature, masochism. A better understanding of these layers will help us deduct enlightening conclusions on Erika‘s masochism, and other psychological aspects related to the masochism, which are woven stitch by stitch throughout the book.
Keywords: Elfriede Jelinek; The Piano Teacher; masochism